Are Porous Polymers Practical to Protect Li‐Metal Anodes? ‐ Current Strategies and Future Opportunities. (8th June 2022) - Gao, Shilun; Li, Zhenxi; Liu, Nian; Liu, Guoliang; Yang, Huabin; Cao, Peng‐Fei
Abstract: The practical application of lithium (Li) metal batteries (LMBs) is significantly hindered by the uncontrolled Li dendrite growth and unstable solid electrolyte interphase layer, which leads to low Coulombic efficiency and short cycling lifetime. Constructing protective layers on Li metal surface is demonstrated as a facile and efficient approach to tackle these issues. With superior chemical/electrochemical stability, mechanical robustness, high current density tolerance, and low cost, porous polymers are considered promising candidates as the protective layers toward practical Li‐metal battery applications. In this review, the fundamental mechanisms in stabilizing Li‐metal electrodes, design principles, scalable processing, and recent progress of porous polymers toward practical batteries are thoroughly reviewed and discussed. The purpose of the current review is to analyze whether applying porous polymers as the protective layers is a more promising option of LMBs, and it also discusses how to practically achieve low cost, high‐energy‐density, safe, and long cycle life batteries. Abstract : The fundamental mechanisms, design principles, scalable processing, and recent progress of porous polymer stabilized Li‐metal electrodes toward practical battery applications are thoroughly reviewed and discussed. Perspectives regarding the future research directions on how to use these polymers for practical lithium metal batteries are also be presented.